2017
DOI: 10.1515/dmpt-2016-0034
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity and cytochrome P450 inhibitory activities of Clinacanthus nutans

Abstract: In conclusion, methanol leaves extract of C. nutans exhibited the highest cytotoxic activity against liver cancer cells (Hep-G2). There is a possibility that herb-drug interaction could occur with C. nutans through inhibitory effects on CYP3A4. Additionally, inhibition of C. nutans on CYP2E1 could show anti-carcinogenesis effects in human liver microsomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…However, the same extract was much less toxic to normal 3T3 cells. Further analyses showed that the antiproliferative effects were possibly attributed to the inhibition in activities of CYP3A4 and CYP2E1, two liver enzymes for detoxifying drugs [ 19 ].…”
Section: Effects and Action Mechanism Studies Of C Nutans Extracts On Cancersmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the same extract was much less toxic to normal 3T3 cells. Further analyses showed that the antiproliferative effects were possibly attributed to the inhibition in activities of CYP3A4 and CYP2E1, two liver enzymes for detoxifying drugs [ 19 ].…”
Section: Effects and Action Mechanism Studies Of C Nutans Extracts On Cancersmentioning
confidence: 99%
“…However, the methanolic extract was much less toxic to normal 3T3 cells. The antiproliferative effect was possibly through inhibition in the enzymatic activities of two detoxifying enzymes CYP3A4 and CYP2E1 [ 19 ]. Another study reported the preparation of C. nutans extracts with five different solvents (hexane, chloroform, ethyl acetate, methanol, and water) and examined the anticancer activities on HepG2 cells.…”
Section: Effects and Action Mechanism Studies Of C Nutans Extracts On Cancersmentioning
confidence: 99%
“…Dried C. nutans leaves powder was bought from a nursery located in Kota Bharu, Kelantan andwas extracted according to the method described previously with slight modifications (Quah et al, 2017). For ethanolic extract, 50 mg of a powder sample in 500 mL of 70% ethanol was sonicated for 30 min.…”
Section: Extraction Of Clinacanthus Nutansmentioning
confidence: 99%
“…C. nutans has been widely used as an anticancer remedy without knowing its effects on chemotherapy. A recent study found that methanol extract of C. nutans at different concentrations possesses inhibitory activity on the metabolism of an analgesic drug (aminopyrine) by CYP3A4 (Quah et al, 2017). In this study, polar extracts of C. nutans were evaluated for their phytochemical profiles, antiproliferative activity, and also combination effect with cyclophosphamide on the normal liver cell line.…”
Section: Introductionmentioning
confidence: 99%
“…Dried C. vespertilionis leaves powder was extracted according to method described previously 10 with slight modifications. For ethanolic extract, 50 g of powder sample in 500mL of 70% ethanol was sonicated for 30 minutes before solvent removal at 40 o C using rotary evaporator.…”
Section: Extraction Of C Vespertilionismentioning
confidence: 99%